DOI: 10.1007/978-0-387-09680-3_26
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Sequent Proofs via Multi-Focusing

Abstract: Abstract. The sequent calculus admits many proofs of the same conclusion that differ only by trivial permutations of inference rules. In order to eliminate this "bureaucracy" from sequent proofs, deductive formalisms such as proof nets or natural deduction are usually used instead of the sequent calculus, for they identify proofs more abstractly and geometrically. In this paper we recover permutative canonicity directly in the cut-free sequent calculus by generalizing focused sequent proofs to admit multiple f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 15 publications
1
51
0
Order By: Relevance
“…While proof-nets and focalized proofs are the results of diverging choices of prooftheoretical design (parallelism versus hypersequentiality), this suggests that they actually may be dierent aspects of the same phenomenon as already advocated in the study of multi-focusing [34].…”
Section: Resultsmentioning
confidence: 95%
“…While proof-nets and focalized proofs are the results of diverging choices of prooftheoretical design (parallelism versus hypersequentiality), this suggests that they actually may be dierent aspects of the same phenomenon as already advocated in the study of multi-focusing [34].…”
Section: Resultsmentioning
confidence: 95%
“…A recent branch of work on maximal multi-focusing (Chaudhuri, Miller, and Saurin 2008a;Chaudhuri, Hetzl, and Miller 2012) has demonstrated that focused proofs can be further restricted to become even more canonical: in each application to a specific logic, the resulting representations are equivalent to existing representations capturing the identity of proofs -proof nets for linear logic, expansion proofs for classical logic. Scherer and Rémy (2015) applied focusing to the λ-calculus with non-empty sums.…”
Section: Focusingmentioning
confidence: 99%
“…Logicians introduced maximal multi-focusing (Chaudhuri, Miller, and Saurin 2008a) to quotient over those reorderings, and Scherer and Rémy (2015) expressed this in a programming setting as saturation. The idea of maximal multi-focusing is to force each noninvertible phase to happen as early as possible in a term, in parallel, removing the potential for reordering them.…”
Section: Saturated Focused λ-Calculusmentioning
confidence: 99%
“…Approaches such as focusing [3], [5] reduce the number of instances of duplicated search, but do not ultimately solve the problem. The authors are not aware of an inductive, bottom-up search algorithm that matches our complexity.…”
Section: Efficient Provability and Proof Searchmentioning
confidence: 99%